Impact of microcredit on women empowerment in Ishwarganj upazila of Mymensingh district in Bangladesh - Nahar, K; Haque, S; Yeasmin, F; Nahar, K; Zaman, N (Progressive Agriculture, 2019)
Women are considered as a medium to provide microcredit in Bangladesh, who are at the same time culturally less recognized, face social obstacles and economically more vulnerable. However, many researches indicated that the status and power of women has much improved since Grameen Bank opened its doors forty years ago. Despite some critics, majority of the scholars reached to the conclusion that microcredit loans encouraged poor women and significantly increased their self-esteem and self-worth, and thereby empowered them. This study evaluates the effects of microcredit on women empowerment at Ishwarganj upazila of Mymensingh district in Bangladesh. The data was collected by using a structured questionnaire. A total 60 sample respondents were selected purposively. Empowerment was measured by five domains (production, resources, income, leadership and time). The score was positive as maximum of them achieved the desired score. The results showed that most of the females who availed the facility of microcredit finally got socioeconomic empowerment through acquiring the self-esteem, confidence level, decision making power, etc., but the question is: is it the same voice that the researchers and the researched people speak? The findings showed that microcredit might play significant impact on the uplift of socio-economic empowerment of the borrowers but we must be careful before reaching to the conclusion. Progressive Agriculture 30 (1): 86-94, 2019